Effect of photodynamic therapy on the healing of a rat skin flap and its implication for head and neck reconstructive surgery - Kübler, Alexander; Finley III, Robert K.; Born, Ivan Antonio; Mang, Thomas S. (Lasers in surgery and medicine, 1996)
Background and Objective Photodynamic therapy (PDT) may as adjuvant therapy be used to reduce tumor recurrence in the head and neck with surgery, given intraoperatively after resection. A concern with the use of intraoperative PDT is the possible effect on wound healing, especially on the healing of myocutaneous skin flaps, which are widely used to reconstruct defects following resections for head and neck cancer. Study Design/Materials and Methods A flap, based on the inferior epigastric artery, was prepared in thirty male Lewis rats. Group I did not receive any further treatment but the wound was left open for 20 minutes. Group II was injected with 5mg/kg Photofrin, 48 hours prior to the operation and also did not receive any further treatment. The wound bed and wound borders of group III were treated with 630nm light of different dosages, delivered by an argon dye laser. Animals in group IV received 5mg/kg Photofrin 48 hours prior to the operation and their wound beds were treated with the same light dosages as group III. After the treatment all flaps were replaced into the wound bed and the incisions were closed. Biopsies for histological analysis were taken at several time points; and on day 21, biopsies for wound tensile strength measurements were taken. Results The wound healing in group I, II, and III appeared normal and there were no differences seen between these groups. Also, the tensile strength did not differ significantly. The flaps of group IV showed serous effusion, epidermal necrosis, and weaker tensile strength (P = .04 and .02 for the light doses of 50 J/sq cm and 75 J/sq cm respectively) at a specific time point. Conclusion The results of this study demonstrate that PDT given immediately before flap reconstruction will result in delayed wound healing. These results should be considered when contemplating the use of PDT as adjuvant intraoperative therapy for tumor surgery requiring flap reconstruction after ablative surgery. © 1996 Wiley-Liss, Inc.